Implementasi Manajemen Kesiswaan dalam Pembentukan Akhlak Terpuji Siswa di SMP Al-Islam Kartasura - Ferlinda, Asriyah Mega; Mustofa, Triono Ali (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This research aims to address two main aspects: (1) describing the implementation of student management, and (2) describing the cultivation of exemplary character among students at Al-Islam Kartasura Junior High School. The research methodology falls under qualitative research with a field research approach. In conducting this research, the researcher utilizes a phenomenological approach that focuses on analyzing primary and secondary data sources. Data collection techniques in this study include interviews, observations, and documentation. The data validity technique employed by the researcher is source triangulation, in which data is obtained from various sources, including the school principal, vice principal for student affairs, counseling guidance team, as well as the supervisors of extracurricular activities and the student council (OSIS) at Al-Islam Kartasura Junior High School. The collected data is then analyzed through stages of data reduction, data presentation, and drawing conclusions. The results of this research indicate the presence of established practices at Al-Islam Kartasura Junior High School, including habits of performing Duha and congregational Zuhr prayers, disposing of waste properly, implementing extracurricular activities related to Quranic reading and writing (BTQ), and implementing an excellent class program, namely the Tahfiz program. These established practices are part of the school's implementation of student management in shaping the exemplary character of students at Al-Islam Kartasura Junior High School.